Soils and broad-scale topography predict historical stand structure across Front Range dry conifer forests - Kevin G. Willson; Paula J. Fornwalt; Mike A. Battaglia; Peter M. Brown; Antony S. Cheng; Benjamin Gannon; Wade T. Tinkham (Forest Ecology and Management, 2026)

Different effects of prenatal air pollution exposure on cord blood protein profiles and postnatal lung function in infants born to asthmatic mothers - Carla Rebeca Da Silva Sena; Olga Gorlanova; Noëmi Künstle; Gabriela Martins Costa Gomes; Andrea Marten; Sven Schulzke; Florian Wyler; Vanessa E. Murphy; Paul D. Robinson; Peter D. Sly; Jakob Usemann; Benjamin Stoecklin; et al. (Environmental Research, 2026)

Microplastic and microbial community loading from a wastewater treatment plant to an estuary - Benjamin M. Cotterell; Constance L. Tulloch; Peter Robins; Davey L. Jones; Peter N. Golyshin (Next Research, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Diet of juvenile skipjack herring Alosa chrysochloris : Ontogenetic shifts, predator–prey size ratios and mouth gape allometry - Joshua P. Egan; Peter J. Hundt; Neil P. Rude; Jason A. DeBoer; Benjamin J. Lubinski; Kristopher A. Maxson; Levi E. Solomon; Andrya L. Whitten Harris; Andrew M. Simons (Journal of Fish Biology, 2026)
The skipjack herring Alosa chrysochloris inhabits Gulf of Mexico drainages, primarily the Mississippi River Basin, and estuarine environments in the Gulf of Mexico. The trophic ecology of the skipjack herring is poorly understood, therefore we quantified the length, mouth gape and gut contents of juvenile skipjack herring from the Mississippi River (fish n = 6), Illinois River (fish n = 181) and Ohio River (fish n = 255) and tested for changes in diets and predator–prey size ratios during ontogeny. We identified statistically significant changes in prey type consumption during ontogeny. Aquatic insects dominated the diets of skipjack herring 40 mm SL were primarily composed of fishes. The most prevalent fish species consumed by skipjack herring were invasive bigheaded carps Hypophthalmichthys spp. and preliminary evidence indicated that inter‐annual variation in the consumption of bigheaded carps was driven by variation in juvenile bigheaded carp abundance. Additional research is needed to determine if the enhancement of native skipjack herring populations could be used as a tool to limit bigheaded carp population sizes. Skipjack herring SL and mouth gape were both significantly positively correlated with maximum, median and minimum sizes of prey consumed. There were allometric changes in the mouth gape of juvenile skipjack herring, with the ratio of mouth gape to SL increasing until ~80 mm SL, then gradually declining. Maximum mouth gape to SL ratios corresponded to substantial increases in the consumption of fishes, indicating that mouth gape allometry may facilitate the ontogenetic transition to piscivory in the skipjack herring. This study improves our understanding of skipjack herring ecology and provides data that can be incorporated into future ecological and evolutionary research, such as the development of food web models.

Diagnosing Linearity Along the Carbon Cascade in Terrestrial Biosphere Models and Observations - Huanyuan Zhang‐Zheng; Vivek K. Arora; Peter Anthoni; Thomas A. M. Pugh; Atul K. Jain; Wenping Yuan; Yadvinder Malhi; Julia Nabel; Daniel S. Goll; Julia Pongratz; Benjamin Poulter; Anthony P. Walker; et al. (Global Change Biology, 2026)
Elevated carbon dioxide (eCO 2 ) acts as a fertiliser for photosynthesis, driving an increase in gross primary production (GPP). However, it is unclear how effectively increased GPP propagates along the ‘carbon (C) cascade’ to increase net primary production (NPP) and vegetation C stocks ( C veg ) in different plant compartments. Vegetation models were criticised for being overly sensitive to photosynthesis (source‐driven), neglecting sink‐driven processes which may attenuate (or amplify) changes in NPP and vegetation C stocks. Here, we introduce an analytical framework to diagnose linearity ( L ) as ratios of relative changes in linked fluxes and pools. We then apply this framework to 16 models of the TRENDY v11 ensemble and to observation‐based estimates of CO 2 sensitivities. We found widely varying global patterns in L across models. Six models showed a majority of grid cells with larger relative changes in NPP than in GPP ( L NPP:GPP > 1 for > 60% of gridcells), indicating increased vegetation carbon use efficiency under eCO 2 . Only three models had L NPP:GPP 60% of gridcells. Four models showed a majority of gridcells with larger relative changes in estimated steady‐state C veg than in NPP, while five models showed the opposite—in both cases with a large spread of L Cveg*:NPP across grid cells within models. Observations‐based analysis reveals median L Cveg*:NPP C veg , ( L Croot:Cveg > 1) while five models showed the opposite. Most field evidence shows L Croot:Cveg > 1. Widely differing distributions of L among models and links in the C cascade reveal a strong influence of nonlinear behaviour in individual models. However, due to the spread in L , across the whole models ensemble, L deviations from 1 were roughly balanced, leading to an overall linear behaviour of terrestrial C cycle representations in the multi‐model‐mean.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Cultural burning, regime shift, and resilience in North American oak-fire systems - Sara Souther; Clare E. Aslan; Peter Z. Fulé; Andrea Thode; Benjamin Sikes; Melinda M. Adams (Journal of Environmental Management, 2026)

Enhanced forest structural heterogeneity increases functional β-diversity but reduces α- and γ-diversity in soil nematodes - Rike Schwarz; Pia M. Bradler; Anne Chao; Po-Yen Chuang; Marcel Ciobanu; Orsi Decker; Benjamin M. Delory; Peter Dietrich; Sebastian Dittrich; Andreas Fichtner; Ludwig Lettenmaier; Michael Junginger; et al. (Soil Biology and Biochemistry, 2026)

Forest Heterogeneity by Chain Saw: How Between‐Patch Variation in Old Growth Attributes Changes the Metacommunities of Beetles - Oliver Mitesser; Marc W. Cadotte; Akira S. Mori; Fons van der Plas; Anne Chao; Julia Rothacher; Claus Bässler; Mirjana Bevanda; Peter H. W. Biedermann; Pia Bradler; Antonio Castañeda‐Gómez; Orsi Decker; et al. (Ecology Letters, 2026)
Metacommunity theory has expanded our understanding of how spatial dynamics and local interactions influence species communities. Different assembly archetypes, reflecting different roles of species differences, habitat differences, and dispersal have been described, but we lack empirical studies specifically in terrestrial habitats testing which archetype is most important. In a replicated design, we experimentally enhanced structural between‐patch heterogeneity in homogeneous production forests and developed a statistical framework controlling for sample incompleteness to detect different metacommunity processes. Meta‐analyses on > 100 K individuals of > 1.3 K beetle species showed an increase of ~60 species in heterogenized forests at γ‐level promoted by increasing α‐diversity consistent with the mass‐effect and an increase of β‐diversity by ~10% supporting species‐sorting . Additionally, we tested β‐deviations from random assembly as a proxy of neutral processes . Findings indicate that enhancing structural heterogeneity can shift forests from patch‐dynamics dominance towards mass‐effect and species‐sorting , offering a promising pathway to restore biodiversity in managed landscapes.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Co-creating water knowledge: a community perspective - Giulio Castelli; Ben C. Howard; Tanveer M. Adyel; Amir AghaKouchak; Afnan Agramont; Hafzullah Aksoy; Rossella Alba; Pedro H.L. Alencar; Amobichukwu C. Amanambu; Hasnat Aslam; Luna Bharati; Liduin Bos-Burgering; et al. (Hydrological Sciences Journal, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

A quasi-differential measurement of neutron scattering from tantalum between 0.65 MeV and 20 MeV - Gregory J. Siemers; Yaron Danon; Sukhjinder Singh; Katelyn C. Keparutis; Peter J. Brain; Benjamin H. Wang; Adam M. Daskalakis; Devin P. Barry; Michael J. Rapp; Robert C. Block (Annals of Nuclear Energy, 2025)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Admixture Mapping Reveals Evidence for Multiple Mitonuclear Incompatibilities in Swordtail Fish Hybrids - Nemo V. Robles; Benjamin M. Moran; María José Rodríguez Barrera; Gaston I. Jofre; Theresa Gunn; Erik N. K. Iverson; Sofia Beskid; John J. Baczenas; Alisa Sedghifar; Peter Andolfatto; Daniel L. Powell; Yaniv Brandvain; et al. (Molecular Ecology, 2025)
How barriers to gene flow arise between closely related species is one of the oldest questions in evolutionary biology. Classic models in evolutionary biology predict that negative epistatic interactions between variants in the genomes of diverged lineages, known as hybrid incompatibilities, will reduce viability or fertility in hybrids. The genetic architecture of these interactions and the evolutionary paths through which they arise have profound implications for the efficacy of hybrid incompatibilities as barriers to gene flow between species. While these questions have been studied using theoretical approaches for several decades, only recently has it become possible to genetically map larger numbers of hybrid incompatibilities. Here, we use admixture mapping in natural hybrid populations of swordtail fish ( Xiphophorus ) to identify hybrid incompatibilities involving genetic interactions between the mitochondrial and nuclear genomes. We find that at least nine regions of the genome are involved in mitonuclear incompatibilities. These incompatibilities involve interactions between the nuclear genome and the X. malinche mitochondria, the X. birchmanni mitochondria, or both. Moreover, they vary in the strength of selection they experience and the degree to which they limit gene flow in natural hybrid populations. Our results build a deeper understanding of the complex architecture of selection against incompatibilities in naturally hybridising species and highlight an important role of mitonuclear interactions in the evolution of reproductive barriers between closely related species.

Inconsistent short-term effects of enhanced structural complexity on soil microbial properties across German forests - Rike Schwarz; Nico Eisenhauer; Christian Ammer; Pia M. Bradler; Orsi Decker; Benjamin M. Delory; Peter Dietrich; Andreas Fichtner; Yuanyuan Huang; Ludwig Lettenmaier; Michael Junginger; Oliver Mitesser; et al. (Applied Soil Ecology, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

Ventilation of the Bay of Bengal oxygen minimum zone by the Southwest Monsoon Current - Peter M. F. Sheehan; Benjamin G. M. Webber; Alejandra Sanchez-Franks; Bastien Y. Queste (Ocean Science, 2025)
Oxygen minimum zones (OMZs) occupy large areas of the tropical subsurface oceans and substantially alter regional biogeochemical cycles. In particular, the removal rate of bio-available nitrogen (denitrification) from the water column in OMZs is disproportionate to their size. The Bay of Bengal is one of the strongest OMZs in the global oceans; however, variable sources of oxygen prevent the onset of large-scale denitrification. The various oxygen-supply mechanisms that maintain oxygen concentrations in the OMZ above the denitrification threshold are currently unknown. Here, using a combination of multi-platform observations and model simulations, we identify an annual supply of oxygen to the Bay of Bengal in the high-salinity core of the Southwest Monsoon Current, a seasonal circulation feature that flows northward into the bay during the South Asian southwest monsoon (i.e. June–September). Oxygen concentrations within the Southwest Monsoon Current (80–100 µmol kg−1) are higher than those of waters native to the bay (i.e.

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

A Metapopulation Model to Assess Water Management Impacts on the Threatened Australian Lungfish, Neoceratodus forsteri - Charles R. Todd; Andrew J. McDougall; Scott M. C. Raymond; Robin Hale; Timothy R. Brown; John D. Koehn; Henry F. Wootton; Steven G. Brooks; Adrian M. Kitchingman; Tom Espinoza; Benjamin G. Fanson; Peter K. Kind; et al. (Fishes, 2025)
The Australian lungfish, Neoceratodus forsteri, is one of the world’s oldest vertebrate lineages, with a slow life-history and threatened status, requiring immediate conservation efforts. The main threats to lungfish populations are degradation and availability of key macrophyte habitats, water regulation and flow modification. As this long-lived species (at least 77 years) has delayed maturity (mature at 10 years), field monitoring alone will not be enough to inform the challenge of ensuring sustainable populations. A stochastic metapopulation model was developed for the Burnett River (Southeast Queensland, Australia), an important habitat for the lungfish that is a highly regulated system with extensive water infrastructure. The model consists of three interacting populations, where the ecology and biology of the species were translated into an 80-year-class population projection matrix for each population, each with post-development streamflow, habitat and movement rules. The model highlights the longer-term interaction between dams and stream flows on habitat availability and subsequent recruitment. Through a pre-development streamflow, we quantify the impact of high regulation and development on the lungfish population in the Burnett River: a minor decline in the upstream population (e.g., 9.8% decline), a large decline in the middle population (64.2% decline), virtually no change in the downstream population (e.g., 1.2% decline) and a moderate decline in the overall metapopulation (e.g., 22.3% decline). The loss of spawning and feeding habitat remains the main reason for population decline, with implications that the loss will lead to greater pressure on remaining downstream habitat due to combined flow and dam effects and, in turn, to extended periods of recovery of spawning habitat. Our modeling approach substantially advances conservation management of this species, as it can be adapted to suit other populations in other river systems and used to test sensitivity to recovery actions.

Reply to: A commentary on Holocene relative sea-level histories of far-field islands in the mid-Pacific - Fangyi Tan; Aron J. Meltzner; Tanghua Li; Jędrzej M. Majewski; Nicole S. Khan; Peter M. Chutcharavan; Benjamin P. Horton (Quaternary Science Reviews, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Recent sedimentology at the grounding zone of the Kamb Ice stream, West Antarctica and implications for ice shelf extent - Theo Calkin; Gavin B. Dunbar; Cliff Atkins; Andrew Carter; Jason J. Coenen; Shaun Eaves; Catherine E. Ginnane; Nicholas R. Golledge; David M. Harwood; Huw J. Horgan; Benjamin C. Hurwitz; Christina Hulbe; et al. (Quaternary Science Reviews, 2024)

Urban tree cover provides consistent mitigation of extreme heat in arid but not humid cities - Peter C. Ibsen; Benjamin R. Crawford; Lucila M. Corro; Kenneth J. Bagstad; Brandon E. McNellis; George D. Jenerette; Jay E. Diffendorfer (Sustainable Cities and Society, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Plastic pollution and human pathogens: Towards a conceptual shift in risk management at bathing water and beach environments - David M. Oliver; Rebecca Metcalf; Davey L. Jones; Sabine Matallana-Surget; David N. Thomas; Peter Robins; Constance L. Tulloch; Benjamin M. Cotterell; Gwion Williams; Joseph A. Christie-Oleza; Richard S. Quilliam (Water Research, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Selective microbial attachment to LDPE plastic beads during passage through the wastewater network - Constance L. Tulloch; Benjamin M. Cotterell; Igor Pântea; Davey L. Jones; Peter N. Golyshin (Chemosphere, 2024)

Isolation, small population size, and management influence inbreeding and reduced genetic variation in K’gari dingoes - Susan M. Miller; Linda Behrendorff; Benjamin L. Allen; Rose L. Andrew; Guy Ballard; J. William O. Ballard; Kylie M. Cairns; Gabriel C. Conroy; Peter J. S. Fleming; Catherine E. Grueber; Jane Oakey; Deane A. Smith; et al. (Conservation Genetics, 2024)
Small island populations are vulnerable to genetic decline via demographic and environmental stochasticity. In the absence of immigration, founder effects, inbreeding and genetic drift are likely to contribute to local extinction risk. Management actions may also have a greater impact on small, closed populations. The demographic and social characteristics of a species can, however, delay the impact of threats. K’gari, a ~ 1 660 km 2 island off the Australian east coast and UNESCO World Heritage Site (Fraser Island 1842–2023), supports an isolated population of approximately 70–200 dingoes that represent an ideal opportunity to explore the small island paradigm. To examine temporal and spatial patterns of genetic diversity in this population we analysed single nucleotide polymorphism (SNP) genotype data (72 454 SNPS) for 112 K’gari dingoes collected over a 25-year period (1996 to 2020). Genetic diversity was lower in K’gari dingoes than mainland dingoes at the earliest time point in our study and declined significantly following a management cull in 2001. We did not find any spatial genetic patterns on the island, suggesting high levels of genetic connectivity between socially discrete packs. This connectivity, combined with the social structure and behaviour of dingoes, may act in concert to buffer the population from the impacts of genetic drift in the short term. Nevertheless, a general decline in genetic variation via inbreeding and drift has occurred over the past 20 years which we suggest should be considered in any future management planning for the population. Monitoring patterns of genetic variation, together with a clearer understanding of the social ecology of K’gari dingoes, will aid in the development of measurable genetic targets set over ecologically meaningful timelines, and help ensure continued survival of this culturally important population.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Hill–Chao numbers allow decomposing gamma multifunctionality into alpha and beta components - Anne Chao; Chun‐Huo Chiu; Kai‐Hsiang Hu; Fons van der Plas; Marc W. Cadotte; Oliver Mitesser; Simon Thorn; Akira S. Mori; Michael Scherer‐Lorenzen; Nico Eisenhauer; Claus Bässler; Benjamin M. Delory; et al. (Ecology Letters, 2024)
Biodiversity–ecosystem functioning (BEF) research has provided strong evidence and mechanistic underpinnings to support positive effects of biodiversity on ecosystem functioning, from single to multiple functions. This research has provided knowledge gained mainly at the local alpha scale (i.e. within ecosystems), but the increasing homogenization of landscapes in the Anthropocene has raised the potential that declining biodiversity at the beta (across ecosystems) and gamma scales is likely to also impact ecosystem functioning. Drawing on biodiversity theory, we propose a new statistical framework based on Hill–Chao numbers. The framework allows decomposition of multifunctionality at gamma scales into alpha and beta components, a critical but hitherto missing tool in BEF research; it also allows weighting of individual ecosystem functions. Through the proposed decomposition, new BEF results for beta and gamma scales are discovered. Our novel approach is applicable across ecosystems and connects local‐ and landscape‐scale BEF assessments from experiments to natural settings.

Rejuvenation of cerebromicrovascular function in aged mice through heterochronic parabiosis: insights into neurovascular coupling and the impact of young blood factors - Rafal Gulej; Ádám Nyúl-Tóth; Boglarka Csik; Benjamin Petersen; Janet Faakye; Sharon Negri; Siva Sai Chandragiri; Peter Mukli; Andriy Yabluchanskiy; Shannon Conley; Derek M. Huffman; Anna Csiszar; et al. (GeroScience, 2023)

Sediment analysis and historical context of the 2018 Palu-Donggala tsunami deposit, Indonesia - Jędrzej M. Majewski; Adam D. Switzer; Rachel Y.S. Guan; Benazir Benazir; Ella Meilianda; Peter R. Parham; Robert Weiss; Stacey S. Martin; Lillian K. Pearson; Jessica E. Pilarczyk; Patrick Daly; Benjamin P. Horton (Marine Geology, 2023)

Fish avoidance of ships during acoustic surveys tested with quiet uncrewed surface vessels - Thomas M. Evans; Lars G. Rudstam; Suresh A. Sethi; David M. Warner; S. Dale Hanson; Benjamin Turschak; Steven A. Farha; Andrew R. Barnard; Daniel L. Yule; Mark R. DuFour; Timothy P. O’Brien; Kevin N. McDonnell; et al. (Fisheries Research, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Holocene relative sea-level histories of far-field islands in the mid-Pacific - Fangyi Tan; Nicole S. Khan; Tanghua Li; Aron J. Meltzner; Jędrzej Majewski; Nicholas Chan; Peter M. Chutcharavan; Niamh Cahill; Matteo Vacchi; Dongju Peng; Benjamin P. Horton (Quaternary Science Reviews, 2023)

The Asymmetric Response Concept explains ecological consequences of multiple stressor exposure and release - Matthijs Vos; Daniel Hering; Mark O. Gessner; Florian Leese; Ralf B. Schäfer; Ralph Tollrian; Jens Boenigk; Peter Haase; Rainer Meckenstock; Daria Baikova; Helena Bayat; Arne Beermann; et al. (Science of The Total Environment, 2023)

Enhancing the structural diversity between forest patches—A concept and real‐world experiment to study biodiversity, multifunctionality and forest resilience across spatial scales - Jörg Müller; Oliver Mitesser; Marc W. Cadotte; Fons van der Plas; Akira S. Mori; Christian Ammer; Anne Chao; Michael Scherer‐Lorenzen; Petr Baldrian; Claus Bässler; Peter Biedermann; Simone Cesarz; et al. (Global Change Biology, 2023)
Intensification of land use by humans has led to a homogenization of landscapes and decreasing resilience of ecosystems globally due to a loss of biodiversity, including the majority of forests. Biodiversity–ecosystem functioning (BEF) research has provided compelling evidence for a positive effect of biodiversity on ecosystem functions and services at the local (α‐diversity) scale, but we largely lack empirical evidence on how the loss of between‐patch β‐diversity affects biodiversity and multifunctionality at the landscape scale (γ‐diversity). Here, we present a novel concept and experimental framework for elucidating BEF patterns at α‐, β‐, and γ‐scales in real landscapes at a forest management‐relevant scale. We examine this framework using 22 temperate broadleaf production forests, dominated by Fagus sylvatica . In 11 of these forests, we manipulated the structure between forest patches by increasing variation in canopy cover and deadwood. We hypothesized that an increase in landscape heterogeneity would enhance the β‐diversity of different trophic levels, as well as the β‐functionality of various ecosystem functions. We will develop a new statistical framework for BEF studies extending across scales and incorporating biodiversity measures from taxonomic to functional to phylogenetic diversity using Hill numbers. We will further expand the Hill number concept to multifunctionality allowing the decomposition of γ‐multifunctionality into α‐ and β‐components. Combining this analytic framework with our experimental data will allow us to test how an increase in between patch heterogeneity affects biodiversity and multifunctionality across spatial scales and trophic levels to help inform and improve forest resilience under climate change. Such an integrative concept for biodiversity and functionality, including spatial scales and multiple aspects of diversity and multifunctionality as well as physical and environmental structure in forests, will go far beyond the current widely applied approach in forestry to increase resilience of future forests through the manipulation of tree species composition.

Effects of long-term average temperature on cardiovascular disease hospitalizations in an American elderly population - Jochem O. Klompmaker; Francine Laden; Peter James; M Benjamin Sabath; Xiao Wu; Joel Schwartz; Francesca Dominici; Antonella Zanobetti; Jaime E. Hart (Environmental Research, 2023)

A review of coarse mineral dust in the Earth system - Adeyemi Adebiyi; Jasper F. Kok; Benjamin J. Murray; Claire L. Ryder; Jan-Berend W. Stuut; Ralph A. Kahn; Peter Knippertz; Paola Formenti; Natalie M. Mahowald; Carlos Pérez García-Pando; Martina Klose; Albert Ansmann; et al. (Aeolian Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Spatially Explicit Seagrass Extent Mapping Across the Entire Mediterranean - Dimosthenis Traganos; Chengfa Benjamin Lee; Alina Blume; Dimitris Poursanidis; Hrvoje Čižmek; Julie Deter; Vesna Mačić; Monica Montefalcone; Gérard Pergent; Christine Pergent-Martini; Aurora M. Ricart; Peter Reinartz (Frontiers in Marine Science, 2022)
The seagrass Posidonia oceanica is the main habitat-forming species of the coastal Mediterranean, providing millennial-scale ecosystem services including habitat provisioning, biodiversity maintenance, food security, coastal protection, and carbon sequestration. Meadows of this endemic seagrass species represent the largest carbon storage among seagrasses around the world, largely contributing to global blue carbon stocks. Yet, the slow growth of this temperate species and the extreme projected temperature and sea-level rise due to climate change increase the risk of reduction and loss of these services. Currently, there are knowledge gaps in its basin-wide spatially explicit extent and relevant accounting, therefore accurate and efficient mapping of its distribution and trajectories of change is needed. Here, we leveraged contemporary advances in Earth Observation—cloud computing, open satellite data, and machine learning—with field observations through a cloud-native geoprocessing framework to account the spatially explicit ecosystem extent of P. oceanica seagrass across its full bioregional scale. Employing 279,186 Sentinel-2 satellite images between 2015 and 2019, and a human-labeled training dataset of 62,928 pixels, we mapped 19,020 km 2 of P. oceanica meadows up to 25 m of depth in 22 Mediterranean countries, across a total seabed area of 56,783 km 2 . Using 2,480 independent, field-based points, we observe an overall accuracy of 72%. We include and discuss global and region-specific seagrass blue carbon stocks using our bioregional seagrass extent estimate. As reference data collections, remote sensing technology and biophysical modelling improve and coalesce, such spatial ecosystem extent accounts could further support physical and monetary accounting of seagrass condition and ecosystem services, like blue carbon and coastal biodiversity. We envisage that effective policy uptake of these holistic seagrass accounts in national climate strategies and financing could accelerate transparent natural climate solutions and coastal resilience, far beyond the physical location of seagrass beds.

Cryptic extinction risk in a western Pacific lizard radiation - Peter J. McDonald; Rafe M. Brown; Fred Kraus; Philip Bowles; Umilaela Arifin; Samuel J. Eliades; Robert N. Fisher; Maren Gaulke; L. Lee Grismer; Ivan Ineich; Benjamin R. Karin; Camila G. Meneses; et al. (Biodiversity and Conservation, 2022)
Cryptic ecologies, the Wallacean Shortfall of undocumented species’ geographical ranges and the Linnaean Shortfall of undescribed diversity, are all major barriers to conservation assessment. When these factors overlap with drivers of extinction risk, such as insular distributions, the number of threatened species in a region or clade may be underestimated, a situation we term ‘cryptic extinction risk’. The genus Lepidodactylus is a diverse radiation of insular and arboreal geckos that occurs across the western Pacific. Previous work on Lepidodactylus showed evidence of evolutionary displacement around continental fringes, suggesting an inherent vulnerability to extinction from factors such as competition and predation. We sought to (1) comprehensively review status and threats, (2) estimate the number of undescribed species, and (3) estimate extinction risk in data deficient and candidate species, in Lepidodactylus . From our updated IUCN Red List assessment, 60% of the 58 recognized species are threatened (n = 15) or Data Deficient (n = 21), which is higher than reported for most other lizard groups. Species from the smaller and isolated Pacific islands are of greatest conservation concern, with most either threatened or Data Deficient, and all particularly vulnerable to invasive species. We estimated 32 undescribed candidate species and linear modelling predicted that an additional 18 species, among these and the data deficient species, are threatened with extinction. Focusing efforts to resolve the taxonomy and conservation status of key taxa, especially on small islands in the Pacific, is a high priority for conserving this remarkably diverse, yet poorly understood, lizard fauna. Our data highlight how cryptic ecologies and cryptic diversity combine and lead to significant underestimation of extinction risk.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Understanding controls on stanols in lake sediments as proxies for palaeopopulations in Mesoamerica - Benjamin Keenan; Anic Imfeld; Yves Gélinas; Peter M. J. Douglas (Journal of Paleolimnology, 2022)

Perfusion-Based Recellularization of Rat Livers with Islets of Langerhans - Peter Demko; Karl H. Hillebrandt; Hendrik Napierala; Nils Haep; Peter Tang; Joseph M. G. V. Gassner; Martin Kluge; Hannah Everwien; Dietrich Polenz; Anja Reutzel-Selke; Nathanael Raschzok; Johann Pratschke; et al. (Journal of Medical and Biological Engineering, 2022)
Purpose Artificial organs might serve as alternative solutions for whole organ transplantation. Decellularization of a liver provides a non-immunogenic matrix with the advantage of three afferent systems, the portal vein, the hepatic artery and the bile duct. This study aims to evaluate the recellularization of rat livers with islets of Langerhans via the bile duct and the portal vein for the comparison of different perfusion routes. Methods Rat livers were decellularized in a pressure-controlled perfusion manner and repopulated with intact isolated islets of Langerhans via either the portal vein or the bile duct. Results Repopulation via the portal vein showed islet clusters stuck within the vascular system demonstrated by ellipsoid borders of thick reticular tissue around the islet cluster in Azan staining. After recellularization via the bile duct, islets were distributed close to the vessels within the parenchymal space and without a surrounding reticular layer. Large clusters of islets had a diameter of up to 1000 µm without clear shapes. Conclusion We demonstrated the bile duct to be superior to the portal vein for repopulation of a decellularized rat liver with islets of Langerhans. This technique may serve as a bioengineering platform to generate an implantable and functional endocrine neo-pancreas and provide scaffolds with the anatomic benefit of three afferent systems to facilitate co-population of cells.

Sperm whales exhibit variation in echolocation tactics with depth and sea state but not naval sonar exposures - Saana Isojunno; Alexander M. von Benda‐Beckmann; Paul J. Wensveen; Petter H. Kvadsheim; Frans‐Peter A. Lam; Kalliopi C. Gkikopoulou; Viivi Pöyhönen; Peter L. Tyack; Benjamin Benti; Ilias Foskolos; Jacqueline Bort; Miguel Neves; et al. (Marine Mammal Science, 2022)
Auditory masking by anthropogenic noise may impact marine mammals relying on sound for important life functions, including echolocation. Animals have evolved antimasking strategies, but they may not be completely effective or cost‐free. We formulated seven a priori hypotheses on how odontocete echolocation behavior could indicate masking. We addressed six of them using data from 15 tagged sperm whales subject to experimental exposures of pulsed and continuous active sonar (PAS and CAS). Sea state, received single‐pulse sound exposure level (SEL sp ), whale depth and orientation towards surface, and sonar were considered as candidate covariates representing different masking conditions. Echolocation behavior, including buzz duration and search range, varied strongly with depth. After controlling for depth and angle to the surface, the likelihood of buzzing following a click train decreased with sea state ( t = −7.3, p sp , except reduced buzzing consistent with previously reported feeding cessation ( t = −2.26, p = .02). A potential Lombard effect was detected during echolocation with sea state and SEL sp , despite off‐axis measurement and right‐hand censoring due to acoustic clipping. The results are not conclusive on masking effects on sperm whale echolocation, highlighting challenges and opportunities for future anthropogenic masking studies.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Microbial diversity and activity in Southern California salterns and bitterns: analogues for remnant ocean worlds - Benjamin Klempay; Nestor Arandia‐Gorostidi; Anne E. Dekas; Douglas H. Bartlett; Christopher E. Carr; Peter T. Doran; Avishek Dutta; Natalia Erazo; Luke A. Fisher; Jennifer B. Glass; Alexandra Pontefract; Sanjoy M. Som; et al. (Environmental Microbiology, 2021)
Summary Concurrent osmotic and chaotropic stress make MgCl 2 ‐rich brines extremely inhospitable environments. Understanding the limits of life in these brines is essential to the search for extraterrestrial life on contemporary and relict ocean worlds, like Mars, which could host similar environments. We sequenced environmental 16S rRNA genes and quantified microbial activity across a broad range of salinity and chaotropicity at a Mars‐analogue salt harvesting facility in Southern California, where seawater is evaporated in a series of ponds ranging from kosmotropic NaCl brines to highly chaotropic MgCl 2 brines. Within NaCl brines, we observed a proliferation of specialized halophilic Euryarchaeota, which corresponded closely with the dominant taxa found in salterns around the world. These communities were characterized by very slow growth rates and high biomass accumulation. As salinity and chaotropicity increased, we found that the MgCl 2 ‐rich brines eventually exceeded the limits of microbial activity. We found evidence that exogenous genetic material is preserved in these chaotropic brines, producing an unexpected increase in diversity in the presumably sterile MgCl 2 ‐saturated brines. Because of their high potential for biomarker preservation, chaotropic brines could therefore serve as repositories of genetic biomarkers from nearby environments (both on Earth and beyond) making them prime targets for future life‐detection missions.

Leaf manganese concentrations as a tool to assess belowground plant functioning in phosphorus-impoverished environments - Hans Lambers; Ian J. Wright; Caio Guilherme Pereira; Peter J. Bellingham; Lisa Patrick Bentley; Alex Boonman; Lucas A. Cernusak; William Foulds; Sean M. Gleason; Emma F. Gray; Patrick E. Hayes; Robert M. Kooyman; et al. (Plant and Soil, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Plastic Ingestion in Sardines (Sardinops sagax) From Frenchman Bay, Western Australia, Highlights a Problem in a Ubiquitous Fish - Thomas Crutchett; Harriet Paterson; Benjamin M. Ford; Peter Speldewinde (Frontiers in Marine Science, 2020)

Characterizing Exposure to and Sharing Knowledge of Drivers of Environmental Change in the St. Lawrence System in Canada - David Beauchesne; Rémi M. Daigle; Steve Vissault; Dominique Gravel; Andréane Bastien; Simon Bélanger; Pascal Bernatchez; Marjolaine Blais; Hugo Bourdages; Clément Chion; Peter S. Galbraith; Benjamin S. Halpern; et al. (Frontiers in Marine Science, 2020)

Higher than expected CO 2 fertilization inferred from leaf to global observations - Vanessa Haverd; Benjamin Smith; Josep G. Canadell; Matthias Cuntz; Sara Mikaloff‐Fletcher; Graham Farquhar; William Woodgate; Peter R. Briggs; Cathy M. Trudinger (Global Change Biology, 2020)
Several lines of evidence point to an increase in the activity of the terrestrial biosphere over recent decades, impacting the global net land carbon sink (NLS) and its control on the growth of atmospheric carbon dioxide ( c a ). Global terrestrial gross primary production (GPP)—the rate of carbon fixation by photosynthesis—is estimated to have risen by (31 ± 5)% since 1900, but the relative contributions of different putative drivers to this increase are not well known. Here we identify the rising atmospheric CO 2 concentration as the dominant driver. We reconcile leaf‐level and global atmospheric constraints on trends in modeled biospheric activity to reveal a global CO 2 fertilization effect on photosynthesis of 30% since 1900, or 47% for a doubling of c a above the pre‐industrial level. Our historic value is nearly twice as high as current estimates (17 ± 4)% that do not use the full range of available constraints. Consequently, under a future low‐emission scenario, we project a land carbon sink (174 PgC, 2006–2099) that is 57 PgC larger than if a lower CO 2 fertilization effect comparable with current estimates is assumed. These findings suggest a larger beneficial role of the land carbon sink in modulating future excess anthropogenic CO 2 consistent with the target of the Paris Agreement to stay below 2°C warming, and underscore the importance of preserving terrestrial carbon sinks.

State of the science in reconciling top‐down and bottom‐up approaches for terrestrial CO 2 budget - Masayuki Kondo; Prabir K. Patra; Stephen Sitch; Pierre Friedlingstein; Benjamin Poulter; Frederic Chevallier; Philippe Ciais; Josep G. Canadell; Ana Bastos; Ronny Lauerwald; Leonardo Calle; Kazuhito Ichii; et al. (Global Change Biology, 2020)
Robust estimates of CO 2 budget, CO 2 exchanged between the atmosphere and terrestrial biosphere, are necessary to better understand the role of the terrestrial biosphere in mitigating anthropogenic CO 2 emissions. Over the past decade, this field of research has advanced through understanding of the differences and similarities of two fundamentally different approaches: “top‐down” atmospheric inversions and “bottom‐up” biosphere models. Since the first studies were undertaken, these approaches have shown an increasing level of agreement, but disagreements in some regions still persist, in part because they do not estimate the same quantity of atmosphere–biosphere CO 2 exchange. Here, we conducted a thorough comparison of CO 2 budgets at multiple scales and from multiple methods to assess the current state of the science in estimating CO 2 budgets. Our set of atmospheric inversions and biosphere models, which were adjusted for a consistent flux definition, showed a high level of agreement for global and hemispheric CO 2 budgets in the 2000s. Regionally, improved agreement in CO 2 budgets was notable for North America and Southeast Asia. However, large gaps between the two methods remained in East Asia and South America. In other regions, Europe, boreal Asia, Africa, South Asia, and Oceania, it was difficult to determine whether those regions act as a net sink or source because of the large spread in estimates from atmospheric inversions. These results highlight two research directions to improve the robustness of CO 2 budgets: (a) to increase representation of processes in biosphere models that could contribute to fill the budget gaps, such as forest regrowth and forest degradation; and (b) to reduce sink–source compensation between regions (dipoles) in atmospheric inversion so that their estimates become more comparable. Advancements on both research areas will increase the level of agreement between the top‐down and bottom‐up approaches and yield more robust knowledge of regional CO 2 budgets.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Transmission of the frequency components of the vibrational signal of the glassy-winged sharpshooter, Homalodisca vitripennis, within and between grapevines - Shira D. Gordon; Benjamin Tiller; James F. C. Windmill; Rodrigo Krugner; Peter M. Narins (Journal of Comparative Physiology A, 2019)
Unfortunately, Fig. 3 was incorrectly published in the original publication. The correct version of Fig. 3 is updated here.

Transmission of the frequency components of the vibrational signal of the glassy-winged sharpshooter, Homalodisca vitripennis, within and between grapevines - Shira D. Gordon; Benjamin Tiller; James F. C. Windmill; Rodrigo Krugner; Peter M. Narins (Journal of Comparative Physiology A, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Höchstmögliche räumlich-zeitliche Auflösung in der Lichtmikroskopie - Simon Dersch; Benjamin Mayer; Daniel A. O. Rotter; Luis M. Oviedo-Bocanegra; Peter L. Graumann (BIOspektrum, 2019)

Integrating national Red Lists for prioritising conservation actions for European butterflies - Dirk Maes; Rudi Verovnik; Martin Wiemers; Dimitri Brosens; Stoyan Beshkov; Simona Bonelli; Jaroslaw Buszko; Lisette Cantú-Salazar; Louis-Francis Cassar; Sue Collins; Vlad Dincă; Milan Djuric; et al. (Journal of Insect Conservation, 2019)

Climate change impact and adaptation for wheat protein - Senthold Asseng; Pierre Martre; Andrea Maiorano; Reimund P. Rötter; Garry J. O’Leary; Glenn J. Fitzgerald; Christine Girousse; Rosella Motzo; Francesco Giunta; M. Ali Babar; Matthew P. Reynolds; Ahmed M. S. Kheir; et al. (Global Change Biology, 2019)
Wheat grain protein concentration is an important determinant of wheat quality for human nutrition that is often overlooked in efforts to improve crop production. We tested and applied a 32‐multi‐model ensemble to simulate global wheat yield and quality in a changing climate. Potential benefits of elevated atmospheric CO 2 concentration by 2050 on global wheat grain and protein yield are likely to be negated by impacts from rising temperature and changes in rainfall, but with considerable disparities between regions. Grain and protein yields are expected to be lower and more variable in most low‐rainfall regions, with nitrogen availability limiting growth stimulus from elevated CO 2 . Introducing genotypes adapted to warmer temperatures (and also considering changes in CO 2 and rainfall) could boost global wheat yield by 7% and protein yield by 2%, but grain protein concentration would be reduced by −1.1 percentage points, representing a relative change of −8.6%. Climate change adaptations that benefit grain yield are not always positive for grain quality, putting additional pressure on global wheat production.

Large uncertainty in carbon uptake potential of land‐based climate‐change mitigation efforts - Andreas Krause; Thomas A. M. Pugh; Anita D. Bayer; Wei Li; Felix Leung; Alberte Bondeau; Jonathan C. Doelman; Florian Humpenöder; Peter Anthoni; Benjamin L. Bodirsky; Philippe Ciais; Christoph Müller; et al. (Global Change Biology, 2018)
Most climate mitigation scenarios involve negative emissions, especially those that aim to limit global temperature increase to 2°C or less. However, the carbon uptake potential in land‐based climate change mitigation efforts is highly uncertain. Here, we address this uncertainty by using two land‐based mitigation scenarios from two land‐use models ( IMAGE and MA g PIE ) as input to four dynamic global vegetation models ( DGVM s; LPJ ‐ GUESS , ORCHIDEE , JULES , LPJ mL). Each of the four combinations of land‐use models and mitigation scenarios aimed for a cumulative carbon uptake of ~130 GtC by the end of the century, achieved either via the cultivation of bioenergy crops combined with carbon capture and storage ( BECCS ) or avoided deforestation and afforestation ( ADAFF ). Results suggest large uncertainty in simulated future land demand and carbon uptake rates, depending on the assumptions related to land use and land management in the models. Total cumulative carbon uptake in the DGVM s is highly variable across mitigation scenarios, ranging between 19 and 130 GtC by year 2099. Only one out of the 16 combinations of mitigation scenarios and DGVM s achieves an equivalent or higher carbon uptake than achieved in the land‐use models. The large differences in carbon uptake between the DGVM s and their discrepancy against the carbon uptake in IMAGE and MA g PIE are mainly due to different model assumptions regarding bioenergy crop yields and due to the simulation of soil carbon response to land‐use change. Differences between land‐use models and DGVM s regarding forest biomass and the rate of forest regrowth also have an impact, albeit smaller, on the results. Given the low confidence in simulated carbon uptake for a given land‐based mitigation scenario, and that negative emissions simulated by the DGVM s are typically lower than assumed in scenarios consistent with the 2°C target, relying on negative emissions to mitigate climate change is a highly uncertain strategy.

Spatial patterns and climate relationships of major plant traits in the New World differ between woody and herbaceous species - Irena Šímová; Cyrille Violle; Jens‐Christian Svenning; Jens Kattge; Kristine Engemann; Brody Sandel; Robert K. Peet; Susan K. Wiser; Benjamin Blonder; Brian J. McGill; Brad Boyle; Naia Morueta‐Holme; et al. (Journal of Biogeography, 2018)
Aim Despite several recent efforts to map plant traits and to identify their climatic drivers, there are still major gaps. Global trait patterns for major functional groups, in particular, the differences between woody and herbaceous plants, have yet to be identified. Here, we take advantage of big data efforts to compile plant species occurrence and trait data to analyse the spatial patterns of assemblage means and variances of key plant traits. We tested whether these patterns and their climatic drivers are similar for woody and herbaceous plants. Location New World (North and South America). Methods Using the largest currently available database of plant occurrences, we provide maps of 200 × 200 km grid‐cell trait means and variances for both woody and herbaceous species and identify environmental drivers related to these patterns. We focus on six plant traits: maximum plant height, specific leaf area, seed mass, wood density, leaf nitrogen concentration and leaf phosphorus concentration. Results For woody assemblages, we found a strong climate signal for both means and variances of most of the studied traits, consistent with strong environmental filtering. In contrast, for herbaceous assemblages, spatial patterns of trait means and variances were more variable, the climate signal on trait means was often different and weaker. Main conclusion Trait variations for woody versus herbaceous assemblages appear to reflect alternative strategies and differing environmental constraints. Given that most large‐scale trait studies are based on woody species, the strikingly different biogeographic patterns of herbaceous traits suggest that a more synthetic framework is needed that addresses how suites of traits within and across broad functional groups respond to climate.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

The Benefits of Reduced Anthropogenic Climate changE (BRACE): a synthesis - Brian C. O’Neill; James M. Done; Andrew Gettelman; Peter Lawrence; Flavio Lehner; Jean-Francois Lamarque; Lei Lin; Andrew J. Monaghan; Keith Oleson; Xiaolin Ren; Benjamin M. Sanderson; Claudia Tebaldi; et al. (Climatic Change, 2018)

Stammcharakterisierung mittels on-line-Redesign von Experimenten - Benjamin Haby; Florian Glauche; Sebastian Hans; M. Nicolas Cruz-Bournazou; Peter Neubauer (BIOspektrum, 2018)

Incorporating climate change into recovery planning for threatened vertebrate species in southwestern Australia - Barbara A. Stewart; Benjamin M. Ford; Bronte E. Van Helden; J. Dale Roberts; Paul G. Close; Peter C. Speldewinde (Biodiversity and Conservation, 2018)

Vegetation demographics in Earth System Models: A review of progress and priorities - Rosie A. Fisher; Charles D. Koven; William R. L. Anderegg; Bradley O. Christoffersen; Michael C. Dietze; Caroline E. Farrior; Jennifer A. Holm; George C. Hurtt; Ryan G. Knox; Peter J. Lawrence; Jeremy W. Lichstein; Marcos Longo; et al. (Global Change Biology, 2018)
Numerous current efforts seek to improve the representation of ecosystem ecology and vegetation demographic processes within Earth System Models ( ESM s). These developments are widely viewed as an important step in developing greater realism in predictions of future ecosystem states and fluxes. Increased realism, however, leads to increased model complexity, with new features raising a suite of ecological questions that require empirical constraints. Here, we review the developments that permit the representation of plant demographics in ESM s, and identify issues raised by these developments that highlight important gaps in ecological understanding. These issues inevitably translate into uncertainty in model projections but also allow models to be applied to new processes and questions concerning the dynamics of real‐world ecosystems. We argue that stronger and more innovative connections to data, across the range of scales considered, are required to address these gaps in understanding. The development of first‐generation land surface models as a unifying framework for ecophysiological understanding stimulated much research into plant physiological traits and gas exchange. Constraining predictions at ecologically relevant spatial and temporal scales will require a similar investment of effort and intensified inter‐disciplinary communication.

Multi‐model comparison highlights consistency in predicted effect of warming on a semi‐arid shrub - Katherine M. Renwick; Caroline Curtis; Andrew R. Kleinhesselink; Daniel Schlaepfer; Bethany A. Bradley; Cameron L. Aldridge; Benjamin Poulter; Peter B. Adler (Global Change Biology, 2018)
A number of modeling approaches have been developed to predict the impacts of climate change on species distributions, performance, and abundance. The stronger the agreement from models that represent different processes and are based on distinct and independent sources of information, the greater the confidence we can have in their predictions. Evaluating the level of confidence is particularly important when predictions are used to guide conservation or restoration decisions. We used a multi‐model approach to predict climate change impacts on big sagebrush ( Artemisia tridentata ), the dominant plant species on roughly 43 million hectares in the western United States and a key resource for many endemic wildlife species. To evaluate the climate sensitivity of A. tridentata , we developed four predictive models, two based on empirically derived spatial and temporal relationships, and two that applied mechanistic approaches to simulate sagebrush recruitment and growth. This approach enabled us to produce an aggregate index of climate change vulnerability and uncertainty based on the level of agreement between models. Despite large differences in model structure, predictions of sagebrush response to climate change were largely consistent. Performance, as measured by change in cover, growth, or recruitment, was predicted to decrease at the warmest sites, but increase throughout the cooler portions of sagebrush's range. A sensitivity analysis indicated that sagebrush performance responds more strongly to changes in temperature than precipitation. Most of the uncertainty in model predictions reflected variation among the ecological models, raising questions about the reliability of forecasts based on a single modeling approach. Our results highlight the value of a multi‐model approach in forecasting climate change impacts and uncertainties and should help land managers to maximize the value of conservation investments.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Plant community structure and nitrogen inputs modulate the climate signal on leaf traits - Benjamin Borgy; Cyrille Violle; Philippe Choler; Pierre Denelle; François Munoz; Jens Kattge; Sandra Lavorel; Jessy Loranger; Bernard Amiaud; Michael Bahn; Peter M. van Bodegom; Henry Brisse; et al. (Global Ecology and Biogeography, 2017)
Aim Leaf traits strongly impact biogeochemical cycles in terrestrial ecosystems. Understanding leaf trait variation along environmental gradients is thus essential to improve the representation of vegetation in Earth system models. Our aims were to quantify relationships between leaf traits and climate in permanent grasslands at a biogeographical scale and to test whether these relationships were sensitive to (a) the level of nitrogen inputs and (b) the inclusion of information pertaining to plant community organization. Location Permanent grasslands throughout France. Methods We combined existing datasets on climate, soil, nitrogen inputs (fertilization and deposition), species composition and four traits, namely specific leaf area, leaf dry matter content and leaf nitrogen and phosphorus concentrations, for 15,865 French permanent grasslands. Trait–climate relationships were tested using the following four climatic variables available across 1,833 pixels (5 km × 5 km): mean annual temperature (MAT) and precipitation (MAP), and two indices accounting for the length of the growing season. We compared these relationships at the pixel level using either using community‐level or species’ trait means. Results Our findings were as follows: (a) leaf traits related to plant nutrient economy shift consistently along a gradient of growing season length accounting for temperature and soil water limitations of plant growth (GSL tw ); (b) weighting leaf traits by species abundance in local communities is pivotal to capture leaf trait–environment relationships correctly at a biogeographical scale; and (c) the relationships between traits and GSL tw weaken for grasslands with a high nitrogen input. Main conclusions The effects of climate on plant communities are better described using composite descriptors than coarse variables such as MAT or MAP, but appear weaker for high‐nitrogen grasslands. Using information at the community level tends to strengthen trait–climate relationships. The interplay of land management, community assembly and bioclimate appears crucial to the prediction of leaf trait variations and their effects on biogeochemical cycles.

The C-2 derivatives of salvinorin A, ethoxymethyl ether Sal B and β-tetrahydropyran Sal B, have anti-cocaine properties with minimal side effects - Amy W.M. Ewald; Peter J. Bosch; Aimee Culverhouse; Rachel Saylor Crowley; Benjamin Neuenswander; Thomas E. Prisinzano; Bronwyn M. Kivell (Psychopharmacology, 2017)

Global patterns in lake ecosystem responses to warming based on the temperature dependence of metabolism - Benjamin M. Kraemer; Sudeep Chandra; Anthony I. Dell; Margaret Dix; Esko Kuusisto; David M. Livingstone; S. Geoffrey Schladow; Eugene Silow; Lewis M. Sitoki; Rashid Tamatamah; Peter B. McIntyre (Global Change Biology, 2017)
Climate warming is expected to have large effects on ecosystems in part due to the temperature dependence of metabolism. The responses of metabolic rates to climate warming may be greatest in the tropics and at low elevations because mean temperatures are warmer there and metabolic rates respond exponentially to temperature (with exponents >1). However, if warming rates are sufficiently fast in higher latitude/elevation lakes, metabolic rate responses to warming may still be greater there even though metabolic rates respond exponentially to temperature. Thus, a wide range of global patterns in the magnitude of metabolic rate responses to warming could emerge depending on global patterns of temperature and warming rates. Here we use the Boltzmann–Arrhenius equation, published estimates of activation energy, and time series of temperature from 271 lakes to estimate long‐term (1970–2010) changes in 64 metabolic processes in lakes. The estimated responses of metabolic processes to warming were usually greatest in tropical/low‐elevation lakes even though surface temperatures in higher latitude/elevation lakes are warming faster. However, when the thermal sensitivity of a metabolic process is especially weak, higher latitude/elevation lakes had larger responses to warming in parallel with warming rates. Our results show that the sensitivity of a given response to temperature (as described by its activation energy) provides a simple heuristic for predicting whether tropical/low‐elevation lakes will have larger or smaller metabolic responses to warming than higher latitude/elevation lakes. Overall, we conclude that the direct metabolic consequences of lake warming are likely to be felt most strongly at low latitudes and low elevations where metabolism‐linked ecosystem services may be most affected.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Moving Towards a New Urban Systems Science - Peter M. Groffman; Mary L. Cadenasso; Jeannine Cavender-Bares; Daniel L. Childers; Nancy B. Grimm; J. Morgan Grove; Sarah E. Hobbie; Lucy R. Hutyra; G. Darrel Jenerette; Timon McPhearson; Diane E. Pataki; Steward T. A. Pickett; et al. (Ecosystems, 2017)

K+ channel signaling in irradiated tumor cells - Benjamin Stegen; Lukas Klumpp; Milan Misovic; Lena Edalat; Marita Eckert; Dominik Klumpp; Peter Ruth; Stephan M. Huber (European Biophysics Journal, 2016)

Phylogenomics at the tips: inferring lineages and their demographic history in a tropical lizard, Carlia amax - Sally Potter; Jason G. Bragg; Benjamin M. Peter; Ke Bi; Craig Moritz (Molecular Ecology, 2016)
High‐throughput sequencing approaches offer opportunities to better understand the evolutionary processes driving diversification, particularly in nonmodel organisms. In particular, the 100–1000's of loci that can now be sequenced are providing unprecedented power in population, speciation and phylogenetic studies. Here, we apply an exon capture approach to generate >99% complete sequence and SNP data across >2000 loci from a tropical skink, Carlia amax , and exploit these data to identify divergent lineages and infer their relationships and demographic histories. This is especially relevant to low‐dispersal tropical taxa that often have cryptic diversity and spatially dynamic histories. For C. amax , clustering of nuclear SNP s and coalescent‐based species delimitation analyses identify four divergent lineages, one fewer than predicted based on geographically coherent mt DNA clades (>9.4% sequence divergence). Three of these lineages are widespread and parapatric on the mainland, whereas the most divergent is restricted to islands off the northeast Northern Territory. Tests for population expansion reject an equilibrium isolation‐by‐distance model for two of the three widespread lineages and infer refugial expansion sources in the relatively mesic northeast Top End and northwest Kimberley. The latter is already recognized as a hotspot of endemism, but our results also suggest that a stronger focus on the northeast Top End, and adjacent islands is warranted. More generally, our results show how genome‐reduction methods such as exon capture can yield insights into the pattern and dynamics of biodiversity across complex landscapes with as yet poorly understood biogeographic history and how exon data can link between population and phylogenetic questions.

Inferring speciation history in the Andes with reduced‐representation sequence data: an example in the bay‐backed antpittas (Aves; Grallariidae; Grallaria hypoleuca s. l.) - Benjamin M. Winger; Peter A. Hosner; Gustavo A. Bravo; Andrés M. Cuervo; Natalia Aristizábal; Luis E. Cueto; John M. Bates (Molecular Ecology, 2015)
In the Andes, humid‐forest organisms frequently exhibit pronounced genetic structure and geographic variation in phenotype, often coincident with physical barriers to dispersal. However, phylogenetic relationships of clades have often been difficult to resolve due to short internodes. Consequently, even in taxa with well‐defined genetic structure, the temporal and geographic sequences of dispersal and vicariance events that led to this differentiation have remained opaque, hindering efforts to test the association between diversification and earth history and to understand the assembly of species‐rich communities on Andean slopes. Here, we use mitochondrial DNA and thousands of short‐read sequences generated with genotyping by sequencing ( GBS ) to examine the geographic history of speciation in a lineage of passerine birds found in the humid forest of the Andes, the ‘bay‐backed’ antpitta complex ( Grallaria hypoleuca s. l). Mitochondrial DNA genealogies documented genetic structure among clade but were poorly resolved at nodes relevant for biogeographic inference. By contrast, relationships inferred from GBS loci were highly resolved and suggested a biogeographic history in which the ancestor originated in the northern Andes and dispersed south. Our results are consistent with a scenario of vicariant speciation wherein the range of a widespread ancestor was fragmented as a result of geologic or climatic change, rather than a stepping‐stone series of dispersal events across pre‐existing barriers. However, our study also highlights challenges of distinguishing dispersal‐mediated speciation from static vicariance. Our results further demonstrate the substantial evolutionary timescale over which the diverse biota of the Andes was assembled.

Using Ecological Thresholds to Inform Resource Management: Current Options and Future Possibilities - Melissa M. Foley; Rebecca G. Martone; Michael D. Fox; Carrie V. Kappel; Lindley A. Mease; Ashley L. Erickson; Benjamin S. Halpern; Kimberly A. Selkoe; Peter Taylor; Courtney Scarborough (Frontiers in Marine Science, 2015)

Linking environmental filtering and disequilibrium to biogeography with a community climate framework - Benjamin Blonder; David Nogués-Bravo; Michael K. Borregaard; John C. Donoghue II; Peter M. Jørgensen; Nathan J. B. Kraft; Jean-Philippe Lessard; Naia Morueta-Holme; Brody Sandel; Jens-Christian Svenning; Cyrille Violle; Carsten Rahbek; et al. (Ecology, 2015)
We present a framework to measure the strength of environmental filtering and disequilibrium of the species composition of a local community across time, relative to past, current, and future climates. We demonstrate the framework by measuring the impact of climate change on New World forests, integrating data for climate niches of more than 14 000 species, community composition of 471 New World forest plots, and observed climate across the most recent glacial–interglacial interval. We show that a majority of communities have species compositions that are strongly filtered and are more in equilibrium with current climate than random samples from the regional pool. Variation in the level of current community disequilibrium can be predicted from Last Glacial Maximum climate and will increase with near‐future climate change.

Global relationship of wood and leaf litter decomposability: the role of functional traits within and across plant organs - Katherina A. Pietsch; Kiona Ogle; Johannes H. C. Cornelissen; William K. Cornwell; Gerhard Bönisch; Joseph M. Craine; Benjamin G. Jackson; Jens Kattge; Duane A. Peltzer; Josep Penuelas; Peter B. Reich; David A. Wardle; et al. (Global Ecology and Biogeography, 2014)
Aim Recent meta‐analyses have revealed that plant traits and their phylogenetic history influence decay rates of dead wood and leaf litter, but it remains unknown if decay rates of wood and litter covary over a wide range of tree species and across ecosystems. We evaluated the relationships between species‐specific wood and leaf litter decomposability, as well as between wood and leaf traits that control their respective decomposability. Location Global. Methods We compiled data on rates of wood and leaf litter decomposition for 324 and 635 tree species, respectively, and data on six functional traits for both organs. We used hierarchical Bayesian meta‐analysis to estimate, for the first time, species‐specific values for wood and leaf litter decomposability standardized to reference conditions ( k * wood and k * leaf ) across the globe. With these data, we evaluated the relationships: (1) between wood and leaf traits, (2) between each k * and the selected traits within and across organs, and (3) between wood and leaf k *. Results Across all species k * wood and k * leaf were positively correlated, phylogenetically clustered and correlated with plant functional traits within and across organs. k * of both organs was usually better described as a function of within‐ and cross‐organ traits, than of within‐organ traits alone. When analysed for angiosperms and gymnosperms separately, wood and leaf k * were no longer significantly correlated, but each k * was still significantly correlated to the functional traits. Main conclusions We demonstrate important relationships among wood and leaf litter decomposability as after‐life effects of traits from the living plants. These functional traits influence the decomposability of senesced tissue which could potentially lead to alterations in the rates of biogeochemical cycling, depending on the phylogenetic structure of the species pool. These results provide crucial information for a better representation of decomposition rates in dynamic global vegetation models.

H-Cluster assembly during maturation of the [FeFe]-hydrogenase - Joan B. Broderick; Amanda S. Byer; Kaitlin S. Duschene; Benjamin R. Duffus; Jeremiah N. Betz; Eric M. Shepard; John W. Peters (JBIC Journal of Biological Inorganic Chemistry, 2014)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Climate change effects on animal and plant phylogenetic diversity in southern Africa - Dorothea V. Pio; Robin Engler; H. Peter Linder; Ara Monadjem; Fenton P.D. Cotterill; Peter J. Taylor; M. Corrie Schoeman; Benjamin W. Price; Martin H. Villet; Geeta Eick; Nicolas Salamin; Antoine Guisan (Global Change Biology, 2014)
Much attention has been paid to the effects of climate change on species' range reductions and extinctions. There is however surprisingly little information on how climate change driven threat may impact the tree of life and result in loss of phylogenetic diversity ( PD ). Some plant families and mammalian orders reveal nonrandom extinction patterns, but many other plant families do not. Do these discrepancies reflect different speciation histories and does climate induced extinction result in the same discrepancies among different groups? Answers to these questions require representative taxon sampling. Here, we combine phylogenetic analyses, species distribution modeling, and climate change projections on two of the largest plant families in the Cape Floristic Region (Proteaceae and Restionaceae), as well as the second most diverse mammalian order in Southern Africa (Chiroptera), and an herbivorous insect genus ( Platypleura ) in the family Cicadidae to answer this question. We model current and future species distributions to assess species threat levels over the next 70 years, and then compare projected with random PD survival. Results for these animal and plant clades reveal congruence. PD losses are not significantly higher under predicted extinction than under random extinction simulations. So far the evidence suggests that focusing resources on climate threatened species alone may not result in disproportionate benefits for the preservation of evolutionary history.

Global patterns of apparent copy number variation in birds revealed by cross-species comparative genomic hybridization - Benjamin M. Skinner; Abdullah Al Mutery; Deborah Smith; Martin Völker; Nilofour Hojjat; Sannaa Raja; Steven Trim; Peter Houde; William J. Boecklen; Darren K. Griffin (Chromosome Research, 2014)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

Alternaria toxins alternariol and alternariol monomethyl ether in grain foods in Canada - Peter M. Scott; Wendy Zhao; Sherry Feng; Benjamin P.-Y. Lau (Mycotoxin Research, 2012)

Stress State and Strain Rate Dependence of the Human Placenta - Benjamin C. Weed; Ali Borazjani; Sourav S. Patnaik; R. Prabhu; M. F. Horstemeyer; Peter L. Ryan; Thomas Franz; Lakiesha N. Williams; Jun Liao (Annals of Biomedical Engineering, 2012)

Transposon proliferation in an asexual parasitoid - KEN KRAAIJEVELD; BRECHTJE ZWANENBURG; BENJAMIN HUBERT; CRISTINA VIEIRA; SYLVIA De PATER; JACQUES J. M. Van ALPHEN; JOHAN T. Den DUNNEN; PETER De KNIJFF (Molecular Ecology, 2012)
The widespread occurrence of sex is one of the most elusive problems in evolutionary biology. Theory predicts that asexual lineages can be driven to extinction by uncontrolled proliferation of vertically transmitted transposable elements (TEs), which accumulate because of the inefficiency of purifying selection in the absence of sex and recombination. To test this prediction, we compared genome‐wide TE load between a sexual lineage of the parasitoid wasp Leptopilina clavipes and a lineage of the same species that is rendered asexual by Wolbachia ‐induced parthenogenesis. We obtained draft genome sequences at 15–20× coverage of both the sexual and the asexual lineages using next‐generation sequencing. We identified transposons of most major classes in both lineages. Quantification of TE abundance using coverage depth showed that copy numbers in the asexual lineage exceeded those in the sexual lineage for DNA transposons, but not LTR and LINE‐like elements. However, one or a small number of gypsy ‐like LTR elements exhibited a fourfold higher coverage in the asexual lineage. Quantitative PCR showed that high loads of this gypsy ‐like TE were characteristic for 11 genetically distinct asexual wasp lineages when compared to sexual lineages. We found no evidence for an overall increase in copy number for all TE types in asexuals as predicted by theory. Instead, we suggest that the expansions of specific TEs are best explained as side effects of (epi)genetic manipulations of the host genome by Wolbachia. Asexuality is achieved in a myriad of ways in nature, many of which could similarly result in TE proliferation.

Simulating the diurnal cycle of rainfall in global climate models: resolution versus parameterization - Paul A. Dirmeyer; Benjamin A. Cash; James L. Kinter; Thomas Jung; Lawrence Marx; Masaki Satoh; Cristiana Stan; Hirofumi Tomita; Peter Towers; Nils Wedi; Deepthi Achuthavarier; Jennifer M. Adams; et al. (Climate Dynamics, 2012)

Reconstruction of past methane availability in an Arctic Alaska wetland indicates climate influenced methane release during the past ~12,000 years - Matthew J. Wooller; John W. Pohlman; Benjamin V. Gaglioti; Peter Langdon; Miriam Jones; Katey M. Walter Anthony; Kevin W. Becker; Kai-Uwe Hinrichs; Marcus Elvert (Journal of Paleolimnology, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Distinguishing between population bottleneck and population subdivision by a Bayesian model choice procedure - BENJAMIN M. PETER; DANIEL WEGMANN; LAURENT EXCOFFIER (Molecular Ecology, 2010)
Although most natural populations are genetically subdivided, they are often analysed as if they were panmictic units. In particular, signals of past demographic size changes are often inferred from genetic data by assuming that the analysed sample is drawn from a population without any internal subdivision. However, it has been shown that a bottleneck signal can result from the presence of some recent immigrants in a population. It thus appears important to contrast these two alternative scenarios in a model choice procedure to prevent wrong conclusions to be made. We use here an Approximate Bayesian Computation (ABC) approach to infer whether observed patterns of genetic diversity in a given sample are more compatible with it being drawn from a panmictic population having gone through some size change, or from one or several demes belonging to a recent finite island model. Simulations show that we can correctly identify samples drawn from a subdivided population in up to 95% of the cases for a wide range of parameters. We apply our model choice procedure to the case of the chimpanzee ( Pan troglodytes ) and find conclusive evidence that Western and Eastern chimpanzee samples are drawn from a spatially subdivided population.

The binding of analogs of porphyrins and chlorins with elongated side chains to albumin - Shimshon Ben Dror; Irena Bronshtein; Hana Weitman; Kevin M. Smith; William G. O’Neal; Peter A. Jacobi; Benjamin Ehrenberg (European Biophysics Journal, 2009)

The discriminative stimulus effects of dopamine D2- and D3-preferring agonists in rats - Mikhail N. Koffarnus; Benjamin Greedy; Stephen M. Husbands; Peter Grundt; Amy Hauck Newman; James H. Woods (Psychopharmacology, 2009)

Experimental snowpack reduction alters organic matter and net N mineralization potential of soil macroaggregates in a northern hardwood forest - J. Megan Steinweg; Melany C. Fisk; Benjamin McAlexander; Peter M. Groffman; Janet P. Hardy (Biology and Fertility of Soils, 2008)

Analysis of TaALMT1 traces the transmission of aluminum resistance in cultivated common wheat (Triticum aestivum L.) - Harsh Raman; Peter R. Ryan; Rosy Raman; Benjamin J. Stodart; Kerong Zhang; Peter Martin; Rachel Wood; Takayuki Sasaki; Yoko Yamamoto; Michael Mackay; Diane M. Hebb; Emmanuel Delhaize (Theoretical and Applied Genetics, 2008)

Opium poppy: blueprint for an alkaloid factory - Peter J. Facchini; Jillian M. Hagel; David K. Liscombe; Natalia Loukanina; Benjamin P. MacLeod; Nailish Samanani; Katherine G. Zulak (Phytochemistry Reviews, 2007)

Spring photosynthesis in a cool temperate bog - TIM R. MOORE; PETER M. LAFLEUR; DIANE M. I. POON; BENJAMIN W. HEUMANN; J. W. SEAQUIST; NIGEL T. ROULET (Global Change Biology, 2006)
In northern ecosystems, the onset and growth of spring photosynthesis may have an important influence on the annual carbon (C) budget, yet the controls have not been clearly identified, especially for peatlands. We used a 5‐year set of daily carbon dioxide (CO 2 ) exchange measurements derived from an eddy covariance tower located at Mer Bleue, an ombrotrophic bog near Ottawa, Canada, from March to May [day‐of‐year (DOY) 60–150], 1999–2003. We used half‐hourly measured net ecosystem exchange minus modelled ecosystem respiration to estimate daily photosynthesis, as gross ecosystem production (GEP). The onset of GEP in each year was closely related to the thinning and disappearance of the snow cover, occurring between DOY 86 and 101. GEP increased during the spring, reaching 10‐day average values of between 5 and 9 g CO 2 m −2 day −1 by the end of May. This increase was initially associated with moss activity ( Sphagnum and Polytrichum ), followed by the evergreen shrubs. Peat temperatures in the rooting zone (10–20 cm depth) and increases in shrub leaf nitrogen and chlorophyll a concentrations contributed to this rapid increase in GEP. Examination of moderate‐resolution imaging spectroradiometer (MODIS) images over several years revealed that the temporal resolution (16‐day composites) was inadequate to capture the onset of GEP but estimates of gross primary productivity and photosynthesis from MODIS 8‐day composites for the most part followed the pattern and magnitude of CO 2 exchange observed at the tower.

Enemy release but no evolutionary loss of defence in a plant invasion: an inter-continental reciprocal transplant experiment - Benjamin J. Genton; Peter M. Kotanen; Pierre-Olivier Cheptou; Cindy Adolphe; Jacqui A. Shykoff (Oecologia, 2005)

Natal homing in juvenile loggerhead turtles ( Caretta caretta ) - BRIAN W. BOWEN; ANNA L. BASS; SHAIO‐MEI CHOW; MEREDITH BOSTROM; KAREN A. BJORNDAL; ALAN B. BOLTEN; TOSHINORI OKUYAMA; BENJAMIN M. BOLKER; SHERYAN EPPERLY; ERIN LACASELLA; DONNA SHAVER; MARK DODD; et al. (Molecular Ecology, 2004)
Juvenile loggerhead turtles ( Caretta caretta ) from West Atlantic nesting beaches occupy oceanic (pelagic) habitats in the eastern Atlantic and Mediterranean, whereas larger juvenile turtles occupy shallow (neritic) habitats along the continental coastline of North America. Hence the switch from oceanic to neritic stage can involve a trans‐oceanic migration. Several researchers have suggested that at the end of the oceanic phase, juveniles are homing to feeding habitats in the vicinity of their natal rookery. To test the hypothesis of juvenile homing behaviour, we surveyed 10 juvenile feeding zones across the eastern USA with mitochondrial DNA control region sequences ( N = 1437) and compared these samples to potential source (nesting) populations in the Atlantic Ocean and Mediterranean Sea ( N = 465). The results indicated a shallow, but significant, population structure of neritic juveniles (Φ ST = 0.0088, P = 0.016), and haplotype frequency differences were significantly correlated between coastal feeding populations and adjacent nesting populations (Mantel test R 2 = 0.52, P = 0.001). Mixed stock analyses (using a Bayesian algorithm) indicated that juveniles occurred at elevated frequency in the vicinity of their natal rookery. Hence, all lines of evidence supported the hypothesis of juvenile homing in loggerhead turtles. While not as precise as the homing of breeding adults, this behaviour nonetheless places juvenile turtles in the vicinity of their natal nesting colonies. Some of the coastal hazards that affect declining nesting populations may also affect the next generation of turtles feeding in nearby habitats.

Nitrogen Dynamics in Ice Storm-Damaged Forest Ecosystems: Implications for Nitrogen Limitation Theory - Benjamin Z. Houlton; Charles T. Driscoll; Timothy J. Fahey; Gene E. Likens; Peter M. Groffman; Emily S. Bernhardt; Donald C. Buso (Ecosystems, 2003)

Regeneration in Gap Models: Priority Issues for Studying Forest Responses to Climate Change - David T. Price; Niklaus E. Zimmermann; Peter J. van der Meer; Manfred J. Lexer; Paul Leadley; Irma T. M. Jorritsma; Jörg Schaber; Donald F. Clark; Petra Lasch; Steve McNulty; Jianguo Wu; Benjamin Smith (Climatic Change, 2001)

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Mapping of mouse gamma crystallin genes on chromosome 1 - Loren C. Skow; Maria E. Donner; Shu-Mei Huang; John M. Gardner; Benjamin A. Taylor; Wesley G. Beamer; Peter A. Lalley (Biochemical Genetics, 1988)

Mapping of mouse gamma crystallin genes on chromosome 1 - Loren C. Skow; Maria E. Donner; Shu-Mei Huang; John M. Gardner; Benjamin A. Taylor; Wesley G. Beamer; Peter A. Lalley (Biochemical Genetics, 1988)